Double oxidation-electrochemical oxidation combined process for treating garbage penetrating fluid

The waste permeate is treated through the double-oxidation-electrochemical oxidation combination process, which solves the problem of poor treatment effect in the existing technology, and achieves efficient removal of CODCr and ammonia nitrogen, and achieves the effect of achieving emission standards.

CN119612824AActive Publication Date: 2025-03-14ZHENGZHOU PUBLIC ENVIRONMENTAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411799259.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The prior art has poor treatment effect on garbage permeability and is difficult to meet emission standards.

Method used

The waste permeable liquid is treated by the combination of double oxidation-electrochemical oxidation technology, including pretreatment, double oxidation treatment, porous spherical activated carbon adsorbent adsorbent and electrochemical oxidation.

Benefits of technology

The treatment efficiency of waste permeate was significantly improved, and the removal rates of CODCr and ammonia nitrogen reached 89.4-99.8% and 86.7-99.3% respectively, reaching the emission standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005177624290000091
    Figure BDA0005177624290000091
Patent Text Reader

Abstract

The invention discloses a double oxidation-electrochemical oxidation combined process for treating garbage penetrating fluid, which comprises the following steps: pretreating the garbage penetrating fluid to obtain the pretreated garbage penetrating fluid; carrying out double oxidation treatment on the pretreated garbage penetrating fluid, and filtering to obtain treated fluid A; adding a porous spherical activated carbon adsorbent into the treating fluid A, uniformly mixing, standing, and carrying out air stripping treatment and filtration to obtain treating fluid B; and carrying out electrochemical oxidation on the treatment liquid B, standing, filtering and discharging. The garbage leachate treatment device is used for solving the technical problem that the garbage leachate treatment effect is poor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment, and in particular relates to a double oxidation-electrochemical oxidation combined process for treating garbage leachate. Background Art

[0002] With the acceleration of urbanization and the rapid development of the global economy, the amount of urban garbage has also increased exponentially. Garbage incineration and landfill are important means of urban garbage disposal. Among them, garbage incineration power generation can not only efficiently reduce and harmlessly reduce garbage, but also turn waste into treasure and achieve reuse, so its application is becoming more and more widespread. The use of garbage incineration power generation requires the storage of a large amount of garbage for use, but during the storage process, organic matter will decompose to produce a certain amount of sewage, and combined with precipitation and infiltrating groundwater, these waters will gather to form a large amount of garbage leachate.

[0003] Garbage leachate is wastewater with high concentration of pollutants generated in the process of reprocessing garbage in landfills or incineration plants. These wastewaters usually contain high concentrations of organic matter, ammonia nitrogen, heavy metals and other toxic and hazardous substances, with complex water quality, high concentration of pollutants, and difficulty in degradation. Therefore, the treatment of garbage leachate has always been a difficult problem in the field of environmental protection.

[0004] At present, the traditional treatment of landfill leachate generally adopts biochemical treatment method. However, biochemical treatment method has little effect on COD Cr , the removal effect of ammonia nitrogen is poor, and it is difficult to meet the emission standards. Summary of the invention

[0005] The invention provides a double oxidation-electrochemical oxidation combined process for treating garbage leachate, which is used to solve the technical problem of poor treatment effect on garbage leachate.

[0006] In view of this, the present invention provides a dual oxidation-electrochemical oxidation combined process for treating landfill leachate, comprising the following steps:

[0007] S1: pre-treating the garbage leachate to obtain pre-treated garbage leachate;

[0008] S2: performing double oxidation treatment on the pretreated landfill leachate, and filtering to obtain treated liquid A;

[0009] S3: adding porous spherical activated carbon adsorbent to the treated liquid A, mixing evenly, standing, and then stripping and filtering to obtain treated liquid B;

[0010] S4: electrochemically oxidizing the treated liquid B, allowing it to stand, and discharging it after filtering;

[0011] Among them, the porous spherical activated carbon adsorbent is an aminated modified rosin-based adsorption resin.

[0012] Furthermore, a dual oxidation-electrochemical oxidation combined process for treating landfill leachate comprises the following steps:

[0013] S1: pre-treating the garbage leachate to obtain pre-treated garbage leachate;

[0014] S2: performing double oxidation treatment on the pretreated landfill leachate, and filtering to obtain treated liquid A;

[0015] S3: Add porous spherical activated carbon adsorbent to the treated liquid A, mix well, let stand for 1-2 hours, then blow off for 5-10 minutes, filter, and obtain treated liquid B;

[0016] S4: electrochemically oxidizing the treated liquid B, allowing it to stand, and discharging it after filtering;

[0017] The porous spherical activated carbon adsorbent is an aminated modified rosin-based adsorption resin; the amount of the porous spherical activated carbon adsorbent added in step S3 is 4-8wt% of the garbage leachate.

[0018] Optionally, the specific steps of the pretreatment in step S1 are: allowing the garbage leachate to settle naturally, filtering through a grid, collecting the filtrate, and subjecting the filtrate to oil separation treatment to obtain the pretreated garbage leachate.

[0019] Furthermore, the specific steps of the pretreatment in step S1 are: allowing the garbage leachate to settle naturally for 4-6 hours, filtering through a grid, collecting the filtrate, and subjecting the filtrate to oil separation treatment for 60-100 minutes to obtain the pretreated garbage leachate.

[0020] Optionally, the specific steps of the double oxidation treatment in step S2 are: adding hydrogen peroxide to the pretreated garbage leachate, mixing evenly, letting it stand, and simultaneously performing ultraviolet light irradiation treatment to perform precipitation.

[0021] Furthermore, the specific steps of the double oxidation treatment in step S2 are: adding hydrogen peroxide to the pretreated garbage leachate, mixing evenly, standing for 1-2 hours, and simultaneously irradiating with ultraviolet light for 20-40 minutes to precipitate;

[0022] The amount of hydrogen peroxide added is 10-20wt% of the garbage leachate, the wavelength of the ultraviolet light is 250-260nm, and the power is 500-700w.

[0023] Optionally, the porous spherical activated carbon adsorbent is prepared by the following method: rosin-based adsorption resin and triethylenetetramine are placed in xylene, mixed evenly, heated to raise the temperature, reacted, and after the reaction is completed, cooled, filtered, washed, and dried to obtain the porous spherical activated carbon adsorbent.

[0024] Furthermore, the porous spherical activated carbon adsorbent is prepared by the following method: rosin-based adsorption resin and triethylenetetramine are placed in xylene, mixed evenly, heated to 60-80°C, reacted for 10-14h, and after the reaction is completed, cooled to 22±3°C, filtered, washed with sodium hydroxide solution and water for 3-5 times in sequence, and dried to obtain a porous spherical activated carbon adsorbent;

[0025] The amount of xylene added to each 1g of rosin-based adsorption resin is 3-5mL, and the concentration of the sodium hydroxide solution is 0.1mol / L;

[0026] The rosin-based adsorption resin was prepared by the following method:

[0027] A1: hydrogenated rosin pentaerythritol ester, maleic acid ester, divinylbenzene, azobisisobutyronitrile and polyvinyl alcohol are uniformly mixed to obtain a mixed solution A;

[0028] A2: Sodium lauryl sulfate, polyvinyl alcohol and sodium chloride are placed in water to obtain a mixed solution B;

[0029] A3: Heat the mixed solution B to 50-60°C, add the mixed solution A, mix well, continue heating to 70-90°C, keep constant temperature after white particles appear, solidify for 1-3 hours, filter, wash with water 3-5 times, and dry to obtain a primary product;

[0030] A4: Place the primary product in a potassium hydroxide solution, first ablate it in an air atmosphere for 20-40 minutes, then continue carbonizing it in a nitrogen atmosphere for 2-4 hours, wash it with water for 3-5 times, and dry it to obtain a rosin-based adsorption resin;

[0031] Wherein, in step A1, the weight ratio of hydrogenated rosin pentaerythritol ester to maleic acid ester is 1:(2-4), the weight ratio of hydrogenated rosin pentaerythritol ester to divinylbenzene is 1:(0.4-0.6), the weight ratio of hydrogenated rosin pentaerythritol ester to azobisisobutyronitrile is 1:(0.015-0.018), and the weight ratio of hydrogenated rosin pentaerythritol ester to polyvinyl alcohol is 1:(0.5-0.7); in step A2, the weight ratio of hydrogenated rosin pentaerythritol ester to sodium lauryl sulfate is 1:(0.015-0.018). The weight ratio of hydrogenated rosin pentaerythritol ester to polyvinyl alcohol is 1:(0.005-0.007), the weight ratio of hydrogenated rosin pentaerythritol ester to sodium chloride is 1:(1-1.4), and the weight ratio of the total weight of sodium lauryl sulfate, polyvinyl alcohol, sodium chloride and water is 1:(4-6); in step A4, the amount of potassium hydroxide solution added to each 1g of the primary product is 1-3mL, and the concentration of the potassium hydroxide solution is 1mol / L.

[0032] Optionally, the weight ratio of the triethylenetetramine and the rosin-based adsorption resin is (1-2):1.

[0033] Optionally, the anode of the electrochemical treatment in step S4 is any one of PbO2 / Ti, Ti02 / Ti, and graphite, the cathode is any one of an iron plate, a copper plate, and a zinc plate, and the filler is Mn02-Fe2O3 loaded with modified kaolin.

[0034] Furthermore, the anode of the electrochemical treatment in step S4 is any one of PbO2 / Ti, TiO2 / Ti, and graphite, the cathode is any one of iron plate, copper plate, and zinc plate, and the filler is MnO2-Fe2O3 loaded with modified kaolin; the anode is more preferably TiO2 / Ti, and the cathode is more preferably an iron plate.

[0035] Optionally, the filling amount of the filler per kilogram of garbage leachate is 15-45g.

[0036] Optionally, the current density is 70-80 mA / cm 2 , voltage is 13-18V, electrolysis time is 150-200min, and electrode spacing is 10-18mm.

[0037] Optionally, the filler is prepared by the following method:

[0038] A1: Add ferric nitrate nonahydrate into water and mix well to obtain a mixed solution A;

[0039] A2: Add mixed solution A to the manganese nitrate solution and mix well to obtain mixed solution B;

[0040] A3: Add modified kaolin into mixed solution B, heat to a high temperature, let stand, filter, wash, dry, calcine, and cool to obtain a filler.

[0041] Furthermore, the filler is prepared by the following method:

[0042] A1: Add ferric nitrate nonahydrate into water and mix well to obtain a mixed solution A;

[0043] A2: Add mixed solution A to the manganese nitrate solution and mix well to obtain mixed solution B;

[0044] A3: Add modified kaolin to mixed solution B, heat to 100-120°C, let stand for 4-6 hours, filter, wash with water 3-5 times, dry, heat to 300-400°C, calcine for 1-3 hours, cool to 22±3°C, and obtain a filler;

[0045] Among them, the weight ratio of modified kaolin and ferric nitrate nonahydrate is 1:(0.1-0.3), the weight ratio of ferric nitrate nonahydrate and water in step A1 is 1:(1-3), the weight ratio of modified kaolin and manganese nitrate solution is 1:(0.06-0.1), and the mass fraction of manganese nitrate solution is 50%.

[0046] Optionally, the modified kaolin is prepared by the following method: kaolin is crushed, sieved, calcined, and then soaked in an acid solution, allowed to stand, filtered, washed, and dried to obtain the modified kaolin.

[0047] Furthermore, the modified kaolin is prepared by the following method: pulverizing the kaolin, passing through a 100-mesh sieve, calcining at a temperature of 800-1200° C., then soaking in a 40% hydrochloric acid solution by mass, standing for 12-18 hours, filtering, washing with water for 3-5 times, and drying to obtain the modified kaolin;

[0048] The amount of hydrochloric acid solution added to each gram of kaolin is 3-5 mL.

[0049] It can be seen from the above technical solutions that the embodiments of the present invention have the following advantages:

[0050] 1. The present application adopts the method of pre-treating the garbage leachate to remove the large suspended solids in the garbage leachate, and performs a double oxidation treatment on the pre-treated garbage leachate. Hydrogen peroxide will produce strong oxidizing hydroxyl radicals under the irradiation of ultraviolet light, which can efficiently decompose the cyanide in the coking wastewater and convert it into a low-toxic or non-toxic substance. The cyanide is then adsorbed by a porous spherical activated carbon adsorbent, and finally an electrochemical treatment is performed to oxidize or reduce the pollutants, which can significantly improve the treatment efficiency of the garbage leachate.

[0051] Among them, the porous spherical activated carbon adsorbent is an aminated rosin-based adsorption resin. Rosin is a natural renewable resource. It is chemically modified to prepare a rosin-based adsorption resin with polymerization function. The adsorption mechanism of the rosin-based adsorption resin is hydrogen bonding and pore filling effect. These forces jointly provide the adsorption driving force, so that the rosin-based adsorption resin can effectively adsorb COD in the garbage leachate. Cr , ammonia nitrogen and other organic pollutants; the rosin-based adsorption resin is then modified by amination, and amine groups can be introduced on the surface of the rosin-based adsorption resin, increasing the polarity and surface activity of the rosin-based adsorption resin, thereby further improving the adsorption capacity of organic pollutants; specifically, the amine groups can form hydrogen bonds, electrostatic interactions or coordination bonds with the pollutants, and can also change the pore structure of the rosin-based adsorption resin, increase the specific surface area, and further improve the adsorption performance, which is more conducive to the COD in the landfill leachate. Cr , removal of ammonia nitrogen.

[0052] 2. This application uses a three-dimensional electrode to electrochemically oxidize the landfill leachate. The three-dimensional electrolysis method has a high oxidation characteristic. By forming a voltage difference under the condition of an applied voltage, a redox reaction occurs on the surface of the particle electrode, generating a large number of hydroxyl free radicals. These free radicals have extremely strong oxidizing properties and can destroy toxic and harmful functional groups in the landfill leachate, causing organic matter to open the ring and break the chain, and convert into carbon dioxide and water, which can improve the COD Cr , removal effect of ammonia nitrogen;

[0053] 3. The present application adopts MnO2-Fe2O3 loaded with modified kaolin as filler. The combination of MnO2 and Fe2O3 can produce a synergistic catalytic effect and significantly improve the catalytic oxidation performance. The modified kaolin itself has a certain adsorption capacity and can adsorb organic pollutants in the landfill leachate. In addition, kaolin loaded with MnO2-Fe2O3 can increase the specific surface area, provide more catalytic active sites, further improve the electrochemical activity of the three-dimensional electrode system, and promote the redox reaction on the electrode surface, thereby improving the treatment effect of the landfill leachate.

[0054] 4. The present application modifies kaolin by calcination and acid washing. High temperature calcination can effectively remove organic impurities, volatile substances and part of water in kaolin, thereby increasing the specific surface area of ​​kaolin and improving adsorption; acid washing can remove impurities such as metal oxides and carbonates in kaolin, and can further increase the specific surface area of ​​kaolin. Therefore, modifying kaolin is convenient for improving the treatment effect of landfill leachate. DETAILED DESCRIPTION

[0055] In order to make the technical scheme of the present invention better understood by the personnel of the technical field, the technical scheme in the embodiment of the present invention is clearly and completely described below. Obviously, the described embodiment is only a part of the embodiment of the present invention, rather than all the embodiments. Based on the embodiment in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or can be prepared by existing methods.

[0056] Preparation Example

[0057] Preparation Example 1

[0058] A rosin-based adsorption resin is prepared by the following method:

[0059] A1: 2 kg of hydrogenated rosin pentaerythritol ester, 6 kg of maleic acid ester, 1 kg of divinylbenzene, 0.033 kg of azobisisobutyronitrile and 1.2 kg of polyvinyl alcohol were mixed to obtain a mixed solution A;

[0060] A2: Add 0.012 kg of sodium dodecyl sulfate, 0.012 kg of polyvinyl alcohol, and 2.4 kg of sodium chloride into 12.12 kg of water to obtain a mixed solution B;

[0061] A3: Heat the mixed solution B to 55°C, add the mixed solution A, mix well, continue heating to 80°C, keep constant temperature after white particles appear, solidify for 2 hours, filter, wash with water 5 times, and dry to obtain the primary product;

[0062] A4: Place the primary product in a potassium hydroxide solution with a concentration of 1 mol / L, first ablate it in an air atmosphere for 30 minutes, then continue carbonizing it in a nitrogen atmosphere for 3 hours, wash it with water 4 times, and dry it to obtain a rosin-based adsorption resin; wherein, the amount of potassium hydroxide solution added to every 1 g of the primary product is 2 mL.

[0063] Preparation Example 2

[0064] A porous spherical activated carbon adsorbent is prepared by the following method:

[0065] 1 kg of rosin-based adsorption resin prepared in Preparation Example 1 and 1 kg of triethylenetetramine were put into xylene, mixed evenly, heated to 70°C, and reacted for 12 hours. After the reaction was completed, the mixture was cooled to 25°C, filtered, washed 5 times with 0.1 mol / L sodium hydroxide solution and water, and dried to obtain a porous spherical activated carbon adsorbent.

[0066] Preparation Example 3

[0067] A porous spherical activated carbon adsorbent, which differs from Preparation Example 2 in that the amount of triethylenetetramine added is different. The amount of triethylenetetramine added in Preparation Example 3 is 1.5 kg.

[0068] Preparation Example 4

[0069] A porous spherical activated carbon adsorbent, which differs from Preparation Example 2 in that the amount of triethylenetetramine added is different. The amount of triethylenetetramine added in Preparation Example 4 is 2 kg.

[0070] Preparation Example 5

[0071] A porous spherical activated carbon adsorbent, which differs from Preparation Example 2 in that the amount of triethylenetetramine added is different, and the amount of triethylenetetramine added in Preparation Example 5 is 0.1 kg.

[0072] Preparation Example 6

[0073] A porous spherical activated carbon adsorbent, which differs from Preparation Example 2 in that the amount of triethylenetetramine added is different, and the amount of triethylenetetramine added in Preparation Example 6 is 5 kg.

[0074] Preparation Example 7

[0075] A modified kaolin is prepared by the following method:

[0076] The kaolin was crushed, passed through a 100-mesh sieve, calcined at 1000°C, and then immersed in a 40% by mass hydrochloric acid solution, allowed to stand for 15 hours, filtered, washed with water 5 times, and dried to obtain modified kaolin; wherein the amount of hydrochloric acid solution added to every 1g of kaolin was 4mL.

[0077] Preparation Example 8

[0078] A filling material is prepared by the following method:

[0079] A1: Add 2 kg of ferric nitrate nonahydrate into 4 kg of water and mix well to obtain a mixed solution A;

[0080] A2: Add mixed solution A to 0.8 kg of 50% manganese nitrate solution, mix well, and obtain mixed solution B;

[0081] A3: Add 10 kg of modified kaolin prepared in Preparation Example 7 to mixed solution B, heat to 110°C, let stand for 5 hours, filter, wash with water 5 times, dry, heat to 350°C and roast for 2 hours, cool to 25°C to obtain a filler.

[0082] Example

[0083] Example 1

[0084] A dual oxidation-electrochemical oxidation combined process for treating garbage leachate comprises the following steps:

[0085] S1: 10 kg of garbage leachate is naturally precipitated for 5 hours, filtered through a grid, the filtrate is collected, and the filtrate is subjected to oil separation treatment for 80 minutes to obtain pretreated garbage leachate;

[0086] S2: Add 1.5 kg of hydrogen peroxide to the pretreated garbage leachate, mix well, let stand for 1.5 hours, and use ultraviolet light with a wavelength of 255 nm and a power of 600 W for 30 minutes to precipitate, filter, and obtain treated liquid A;

[0087] S3: Add 0.6 kg of the porous spherical activated carbon adsorbent prepared in Preparation Example 2 to the treated liquid A, mix well, let stand for 1.5 hours, then blow off for 7 minutes, filter, and obtain treated liquid B;

[0088] S4: The anode is PbO2 / Ti, the cathode is iron plate, and the filler is 15g. The three-dimensional electrode prepared in Preparation Example 8 is used at a current density of 75mA / cm 2 Under the conditions of voltage of 15V and electrode spacing of 14mm, the treated liquid B was electrochemically oxidized for 180min and discharged after filtration.

[0089] Embodiment 2-5

[0090] A dual oxidation-electrochemical oxidation combined process for treating garbage leachate, which differs from Example 1 in that the source of the porous spherical activated carbon adsorbent in step S3 is different, and the porous spherical activated carbon adsorbents in Examples 2-5 are prepared using Preparation Examples 3-6, respectively.

[0091] Example 6

[0092] A dual oxidation-electrochemical oxidation combined process for treating garbage leachate, which differs from Example 2 in that the filling amount of the filler in step S4 is different, and the filling amount of the filler in Example 6 is 30g.

[0093] Example 7

[0094] A dual oxidation-electrochemical oxidation combined process for treating garbage leachate, which differs from Example 2 in that the filling amount of the filler in step S4 is different, and the filling amount of the filler in Example 7 is 45g.

[0095] Comparative Example

[0096] Comparative Example 1

[0097] A dual oxidation-electrochemical oxidation combined process for treating garbage leachate, which differs from Example 1 in that the porous spherical activated carbon adsorbent in step S3 is replaced by an equal amount of rosin-based adsorption resin.

[0098] Comparative Example 2

[0099] A dual oxidation-electrochemical oxidation combined process for treating garbage leachate, which differs from Example 1 in that the porous spherical activated carbon adsorbent in step S3 is replaced by polyacrylamide in equal amounts.

[0100] Comparative Example 3

[0101] A dual oxidation-electrochemical oxidation combined process for treating garbage leachate, which differs from Example 1 in that in step S4, MnO2 in the filler is replaced by Fe2O3 in equal amounts.

[0102] Comparative Example 4

[0103] A dual oxidation-electrochemical oxidation combined process for treating garbage leachate, which differs from Example 1 in that Fe2O3 in the filler in step S4 is replaced by MnO2 in equal amounts.

[0104] Comparative Example 5

[0105] A dual oxidation-electrochemical oxidation combined process for treating garbage leachate, which differs from Example 1 in that no filler is added in step S4.

[0106] Performance testing

[0107] The following performance tests were performed on the treated landfill leachate in Examples 1-7 and Comparative Examples 1-5:

[0108] COD Cr :According to CJT428-2013 "Detection Method for Leachate of Domestic Waste", the COD in the treated leachate of garbage Cr The test results are shown in Table 1.

[0109] Ammonia nitrogen: The ammonia nitrogen in the treated garbage leachate was determined according to CJT428-2013 “Detection method for domestic garbage leachate”. The test results are shown in Table 1.

[0110] Among them, COD in the waste leachate before treatment Cr The concentration is 41600 mg / L and the ammonia nitrogen content is 1200 mg / L.

[0111] Table 1 Test results

[0112]

[0113] As can be seen from Table 1, the dual oxidation-electrochemical oxidation combined process for treating garbage leachate in the present application effectively reduces the COD in the garbage leachate through the combined action of each step. cr , ammonia nitrogen content, including COD Cr The removal rate of nitrogen is 89.4-99.8%, and the removal rate of ammonia nitrogen is 86.7-99.3%.

[0114] Combining Example 1 and Comparative Examples 1-2, it can be seen that the COD Cr The removal rate of COD in wastewater was 92.9%, and the removal rate of ammonia nitrogen was 91.3%, which was better than that of comparative examples 1-2, indicating that the porous spherical activated carbon adsorbent was more suitable for aminated rosin-based adsorption resin, which could effectively adsorb COD in wastewater. Cr, ammonia nitrogen and other organic pollutants; after amination modification, amine groups are introduced on the resin surface to increase polarity and surface activity, further improving the adsorption capacity of organic pollutants, thus being more conducive to the adsorption of COD in coking wastewater. Cr , removal of ammonia nitrogen.

[0115] Combining Example 1 and Comparative Examples 3-5, it can be seen that the COD Cr The removal rate of is 92.9%, and the removal rate of ammonia nitrogen is 91.3%, which are better than those of comparative examples 3-5, indicating that the filler is more suitable for MnO2-Fe2O3 loaded with modified kaolin. Through the synergistic effect among the three, the catalytic oxidation activity is further improved, which is more helpful to improve the treatment effect of garbage leachate.

[0116] Combining Examples 1-5, it can be seen that the COD in Example 2 Cr The removal rate of nitrogen and ammonia is 95.3%, and the removal rate of ammonia nitrogen is 94.8%, which are better than other embodiments, indicating that the porous spherical activated carbon adsorbent prepared by Preparation Example 3 is more suitable, and the amount of triethylenetetramine added in Preparation Example 3 is more suitable. When the amount of triethylenetetramine added is too little, the modification effect of the rosin-based adsorption resin is not good, which leads to poor adsorption effect of the porous spherical activated carbon adsorbent; when the amount of triethylenetetramine added is too much, too many amine groups will lead to unstable structure of the rosin-based adsorption resin, resulting in too dense active sites on the surface of the rosin-based adsorption resin, which will reduce the adsorption of organic pollutants, which is not conducive to COD in coking wastewater. Cr , removal of ammonia nitrogen.

[0117] Combining Example 2 and Example 6-7, it can be seen that the COD in Example 6 Cr The removal rate of is 99.8%, and the removal rate of ammonia nitrogen is 99.3%, which are better than other embodiments, indicating that the filling amount of the filler in Example 6 is more appropriate. If the filling amount is small, it cannot play a better role, resulting in a lower electrolysis effect on the garbage leachate; if the filling amount is large, it is easy to cause short-circuit current and covering problems, and will also affect the treatment of the garbage leachate. Therefore, when the filling amount of the filler is within the above range, it can achieve a better treatment effect on the garbage leachate.

[0118] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A dual oxidation-electrochemical oxidation combined process for treating landfill leachate, characterized in that: The steps include: S1: pre-treating the garbage leachate to obtain pre-treated garbage leachate; S2: performing double oxidation treatment on the pretreated landfill leachate, and filtering to obtain treated liquid A; S3: adding porous spherical activated carbon adsorbent to the treated liquid A, mixing evenly, standing, and then stripping and filtering to obtain treated liquid B; S4: electrochemically oxidizing the treated liquid B, allowing it to stand, and discharging it after filtering; Among them, the porous spherical activated carbon adsorbent is an aminated modified rosin-based adsorption resin.

2. The dual oxidation-electrochemical oxidation combined process for treating garbage leachate according to claim 1 is characterized in that: The specific steps of the pretreatment in step S1 are: allowing the garbage leachate to settle naturally, filtering through a grid, collecting the filtrate, and subjecting the filtrate to oil separation treatment to obtain the pretreated garbage leachate.

3. The dual oxidation-electrochemical oxidation combined process for treating garbage leachate according to claim 1 is characterized in that: The specific steps of the double oxidation treatment in step S2 are: adding hydrogen peroxide to the pretreated garbage leachate, mixing evenly, letting it stand, and simultaneously performing ultraviolet light irradiation treatment to perform precipitation.

4. The dual oxidation-electrochemical oxidation combined process for treating garbage leachate according to claim 1 is characterized in that: The porous spherical activated carbon adsorbent is prepared by the following method: rosin-based adsorption resin and triethylenetetramine are put into xylene, mixed evenly, heated, reacted, cooled after the reaction is completed, filtered, washed, and dried to obtain the porous spherical activated carbon adsorbent.

5. The dual oxidation-electrochemical oxidation combined process for treating garbage leachate according to claim 4 is characterized in that: The weight ratio of the triethylenetetramine and the rosin-based adsorption resin is (1-2):

1.

6. The dual oxidation-electrochemical oxidation combined process for treating garbage leachate according to claim 1 is characterized in that: The anode of the electrochemical treatment in step S4 is any one of PbO2 / Ti, TiO2 / Ti, and graphite, the cathode is any one of iron plate, copper plate, and zinc plate, and the filler is MnO2-Fe2O3 loaded with modified kaolin.

7. The dual oxidation-electrochemical oxidation combined process for treating garbage leachate according to claim 6 is characterized in that: The filling amount of the filler in each kilogram of garbage leachate is 15-45g.

8. The dual oxidation-electrochemical oxidation combined process for treating garbage leachate according to claim 6 is characterized in that: The current density is 70-80 mA / cm 2 , voltage is 13-18V, electrolysis time is 150-200min, and electrode spacing is 1O-18mm.

9. The dual oxidation-electrochemical oxidation combined process for treating landfill leachate according to claim 6, characterized in that: The filler is prepared by the following method: A1: Add ferric nitrate nonahydrate into water and mix well to obtain a mixed solution A; A2: Add mixed solution A to the manganese nitrate solution and mix well to obtain mixed solution B; A3: Add modified kaolin into mixed solution B, heat to a high temperature, let stand, filter, wash, dry, calcine, and cool to obtain a filler.

10. The dual oxidation-electrochemical oxidation combined process for treating garbage leachate according to claim 9, characterized in that: The modified kaolin is prepared by the following method: kaolin is crushed, sieved, calcined, then immersed in an acid solution, allowed to stand, filtered, washed, and dried to obtain the modified kaolin.

Citation Information

Patent Citations

  • Asphaltic resin composite spherical activated carbon with expanded graphite enhanced oil absorption property and preparation method therefor

    CN105032349A

  • Double oxidation-electrochemical oxidation combined process for advanced treatment of landfill leachate

    CN112960819A

  • Hydrogenated rosin-based macroporous adsorption resin as well as preparation method and application thereof

    CN115057958A

  • Treatment process of coking wastewater

    CN118458982A

  • Treatment of water to remove cyanobacteria

    WO2022234415A1